Acute lupus pneumonitis resembling miliary tuberculosis: A case-based review - Li Xin; Wang Yuan; Zhang Baoyu; Jia Xiaoxia; Mu Lin; Ke Jing (Open Life Sciences, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune disease involving multiple systems and organs, with pulmonary involvement known to be associated with disease prognosis and mortality. Acute lupus pneumonitis (ALP) resembling miliary tuberculosis (TB) is rare. Here, we present a case of ALP mimicking miliary TB and review the literature. A 19-year-old male student was referred to our hospital with fever. Although the patient met the diagnostic criteria for SLE, diffuse miliary nodules in both lungs were observed on a chest computed tomography scan. A series of tests, including pathological testing of bronchoscopy brushes, T-lymphocyte culture + interferon assay (A + B), tuberculin test, detection of mycobacterium TB DNA, and acid-fast bacilli smear in bronchoalveolar lavage fluid, were unable to confirm the presence of TB infection. We considered the patient to have ALP. After beginning ALP therapy, his symptoms disappeared, and the imaging and hematological results returned to normal. Miliary TB and ALP have similar clinical manifestations and imaging changes, which make diagnosis difficult. This case highlights the need to ensure accurate diagnosis and treatment to improve prognosis.